Lineage-Specific Chiral Biases of Human Embryonic Stem Cells during Differentiation - Worley, Kathryn E. (Stem Cells Int, 2018)
Left-right symmetry breaking is a complex developmental process and an important part of embryonic axis development. As of yet, the biophysical mechanism behind LR asymmetry establishment remains elusive for the overall asymmetry of embryos as well as for the organ-specific asymmetry. Here, we demonstrate that inherent cellular chirality is observable in the cells of early embryonic stages using a 3D Matrigel bilayer system. Differentiation of human embryonic stem cells to three lineages corresponding to heart, intestine, and neural tissues demonstrates phenotype-specific inherent chiral biases, complementing the current knowledge regarding organ development. The existence of inherent cellular chirality early in development and its correlation with organ asymmetry implicate cell chirality as a possible regulator in LR symmetry breaking.